Analysis of Light Vehicle Accident Data at PT Z Period 2018-2022 Using Human Factor Analysis and Classification System-Mining Industry Framework - Aji, Dimas Bayu; Susilowati, Indri Hapsari (Journal of Social Science, 2024)
The mining industry is an industry with high risk characteristics, where human factors are one of the main causes of work accidents. PT Z, is a mineral mining company operating in the Papua region, Indonesia with quite complex operations, ranging from underground mining techniques to various numbers and types of production equipment. With the workforce currently reaching more than 29,563 (February 2023 data), the potential for human interaction with moving vehicles is quite high so that the risk of traffic accidents is something that is currently the company's focus. In the period 2018 to 2022, there have been 513 incidents involving light vehicles. This research, which was conducted at PT Z, aims to examine light vehicle accidents using the Human Factors Analysis and Classification-Mining Industry (HFACS-MI) framework. The research methodology consists of collecting qualitative data on accident cases at PT Z for 5 years, which are included in the classification of light vehicle accidents sourced from the incident management system. Next, the light vehicle accident data will be classified using the HFACS-MI framework, with descriptive statistics for data analysis. Data shows that 88% of light vehicle accidents occur in the highland operating area. Based on the HFACS-MI framework, light vehicle accidents that occurred at PT Z occurred due to contributions from several layers or levels, namely organizational influence factors (106%), unsafe leadership (9%), precondition for unsafe acts (109%) , as well as unsafe acts carried out (77%). It can be concluded that by reducing errors caused by human factors, light vehicle accidents can be reduced in mining operation areas. The HFACS-MI framework is considered effective in analyzing accidents in a structured and standardized manner, especially regarding the contribution of human factors in accidents in the mining industry.